Fluência da fala em diferentes gravidades do desvio fonológico - Costa, Vanessa Pires (2013)
This dissertation is structured in the alternative model according to what has been proposed by MDT (Structure and Presentation of Papers, Dissertations and Theses) UFSM. It is composed of an introduction followed by two scientific articles and, afterwards a discussion integrating the article results is presented. At the end, the final considerations are presented concluding the dissertation. The purpose of this research is to evaluate the speech fluency in speech disordered children, in different severity degrees of the deviation, as well as analyzing a possible relationship between fluency and the phonological system of these children. That is the focus of this research because one believes that the fluency in speech disordered children can be changed as an attenuation of certain speech difficulties. However, there aren t researches relating fluency and the speech disorder severity. The relationship between the disfluency and the phonological system of children is another important question that has been observed in some research results and in the speech pathologist s practice. One believes that speech disordered children present disruptions when faced with the non-acquired sound in their speech, trying to improve its intelligibility. That topic is discussed in the second article of this dissertation. One observed increase of disfluencies according to the severity degree decrease of speech disorder. This probably occurs because in the milder severe degrees, children present more moments of hesitation, trying to approximate their pronunciation to the pattern. On the other hand, children with severe disorder possibly do not present awareness of their own disorder